Kemampuan Membaca Al-Qur’an Perspektif Metode Tilawati Studi Ilmu Pendidikan Islam - Izzan, Ahmad; Albarokah, Syahid (STAI Al-Musaddadiyah Garut, 2024)
The Qur'an was revealed by Allah SWT as a testament to the truth of Prophet Muhammad SAW, with its primary function serving as guidance for humanity. The Qur'an addresses many aspects of education and its importance in human life. The ability to read the Qur'an is a proficiency or skill in correctly and accurately reciting the Qur'anic text or divine speech according to the rules of Tajweed. The Tilawati method is a learning approach for reading the Qur'an that employs tilawah melodies with a balanced approach, combining habituation through classical group practice and precision in reading through individualized techniques with the